41 Association between postoperative infection and blood transfusions in cardiac surgery in king faisal cardiac center, 2016 to 2019. (25th October 2019) - Abukhodair, Abdulkarim Walid; Bennett, Sean; Mosterio, Andreas; Qarni, Mohammed Al; Bukhari, Ziad; Kadi, Ammar; Mufti, Hani; Algarni, Abdullah; Jamalallail, Sahal
Abstract : Background: Blood transfusion is a commonly used therapy in cardiac surgery, whether it is given during the surgery or in the intensive care unit. Because of this alarming number, it is necessary to evaluate the risk and complications that patients are exposed to once transfusion therapy is applied. Postoperative infection in cardiac surgery patients has been linked to patient outcome. Nosocomial pneumonia, surgical site infection, mediastinitis, bacteremia, and sepsis are common infectious processes affecting the outcome. In the King Faisal Cardiac Center (KFCC), the liberal use of blood transfusions has been raising questions on the outcomes of patients. In an attempt to decrease the use of transfusions, it is essential to understand the risk and complications associated with them. Postoperative infection is the main complication that causes most concern. We aimed to determine the effects of blood transfusion on postoperative infection in cardiac surgery patients and to assess the benefits or negatives of our large transfusion rate at the KFCC from January 2017 to January 2019. Methods: We did a retrospective cohort study of all patients aged older than 18 years who underwent cardiac surgery at KFCC from January 2017 to January 2019. Data were analyzed using the statistical package IBM SPSS 22. Categorical variables were reported as percentages, while numerical variables were reported as means and medians. P values less than 0.05 were considered significant. Results: 197 was the sample size. Mean age was 57.64 years and body-mass index (BMI) was 28.91. 93.4% of patients had blood transfused and 31.98% had postoperative infection. Comparing transfused and non-transfused patients, hemoglobin (Hb) on discharge values and postoperative infection were similar; only preoperative Hb was significantly different (p<0.0053). Comparing patients receiving 1–2 units of red blood cells (RBCs; 48%) and more than 2 units of RBCs (52%), there was also no significant difference in postoperative infection. Patients with postoperative infection had a mean HbA1c of 8.16, while non-infected patients had a mean HbA1c of 7.33. Conclusion: Blood transfusion was not significantly linked to postoperative infection and discharge hemoglobin. The findings show us that giving blood has not increased or decreased the risk of infection. Therefore, it is safe to say that, regarding postoperative infection and discharge Hb, we are transfusing too much blood and using up resources for outcomes that could have been achieved otherwise. Although our curiosity for the high infection rate has still not been answered completely, we assume HbA1c plays a major role because of the high prevalence of diabetes, and especially uncontrolled diabetes, in our population.